Testing of a modified Seistec seismic reflection profiler and its application to the marine geology of offshore eastern Oak Island, Mahone Bay, Nova Scotia, Canada - Simpkin, Peter G.; Fader, Gordon B.J. (Atlantic Geoscience, 2024)
A modified, surface-towed, sub-bottom profiler, the boomer-based “Seistec” system, was deployed in an area offshore of eastern Oak Island, Mahone Bay, Nova Scotia, in May 2017. Several grids of lines were surveyed around eastern Oak Island. Subsequently, the sub-bottom profiler data were interpreted from a geological perspective after being processed, scaled, aligned and merged with a previously collected multibeam bathymetric data set. This exercise resulted in the first integration of multibeam bathymetry and high resolution sub-bottom profile data from offshore Oak Island and provides insight into the subsurface stratigraphy of the bedrock and glacial and postglacial sediments. The seabed is mostly composed of boulder-covered till drumlins and Holocene mud. Subsurface sediments include till and glaciomarine and lacustrine sediments, and a regional unconformity developed in response to postglacial transgression was revealed. Anthropogenic features include a shipwreck and unusual coast-normal seabed gravel ridges. Seabed natural features include sinkholes and pockmarks that are likely connected by channels in the bedrock to sinkhole features on adjacent land.